Elaboração e avaliação de produtos cárneos com adição de ingredientes funcionais através de seus efeitos no metabolismo de ratos - Hautrive, Tiffany Prokopp (2014)
There is a trend in the food industry to develop products with functional ingredients which, when consumed, provides benefits to human health. The objective of this research, prepare meat products with dietary fiber and the influence of the consumption of diets containing these products in the metabolic response of rats. This work consisted of two experimental trials. The first was the development of the following beef burgers: traditional (HT); 7.5% of full golden flaxseed flour (HLI); 7.5% defatted golden flaxseed flour (HLD) and 6% chitosan (HQ). In the second trial, chicken sausages were prepared: traditional (ST); with 7.5% defatted golden flaxseed flour (SLD); 7.5% of full golden flaxseed flour (SLI) and 4% chitosan (SQ). In each test, the physico-chemical aspects, sensory and microbiological of manufactured products were analyzed. These formulations were incorporated into experimental diets in order to analyze the protein quality of the processed products and their effects on normolipidemic and normoglycemic rats metabolism. It was found that the burgers with added fiber showed higher protein content and the HT higher lipid content (8.51%). Observing the stability of hamburgers over 90 days storage, it was noted that there was a declining trend of the values of parameters L* and a* values and increased b* and h* parameters. The HQ had a high pH from time zero (6.59). The HLI had TBARS values above 2.0 mg malonaldeído.Kg-1. According to the analysis of protein quality was observed that the true digestibility (DV) of the burgers with fibers was smaller than the HT and ranged from 80.48% (HLD) to 85.68% (HQ). The PER ranged from 2:33 (casein) to 1.94 (HQ) and the NPR 2.65 (casein) to 2.22 (HQ). In the metabolism of the mice was observed that the animals that received HQ showed lower total cholesterol (138.09 mg / dL) than the other groups. For chicken sausages, the percentage of protein was higher in SLD (16.19%) and the fat content and energy in SLI, 8.9% and 174 kcal. The yield of the sausages with fibers is greater than 93%. Unlike burgers with fibers, the sausages showed good acceptability. Checking the oxidative stability of the chicken sausages for 14 days, it was observed that most had SQ pH 6.6 and the lowest ST 6.1. Regarding the values obtained in the microbiological analyzes with the products, were within the tolerances established by the Brazilian legislation for all treatments. The values of the PER of sausages ranged from 1.74 (SLI) and 1.99 (SLD) and the NPR 1.76 (SLD) to 1.53 (SLI). The DV sausages showed greater than 97%. Rats fed diets containing sausage with whole flaxseed flour and defatted had a lower concentration of triglycerides. Analyzing intestinal physiology, the animals fed burgers and sausages with fibers had higher fecal weight, cecal weight and lower fecal pH. In order to launch the technological meat market a product that can demonstrate functional property to assist the functioning of the intestine and its consumption should be associated with a balanced diet and healthy lifestyle and be considered a source of fiber, the burger could be reformulated to better acceptance by consumers. The sausage could be a promising product for sale in a short period of time.